Reminder of issuing variation order of construction for facade curtain works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reminder of issuing variation order of construction for facade curtain works of BRACU new campus project.